FOXO 1 deletion in chondrocytes rescues diabetes-impaired fracture healing by restoring angiogenesis and reducing apoptosis - Alharbi, Mohammed A.; Graves, Dana T. (Frontiers in Endocrinology, 2023)
Introduction Diabetes mellitus is associated with higher risks of long bone and jaw fractures. It is also associated with a higher incidence of delayed union or non-union. Our previous investigations concluded that a dominant mechanism was the premature loss of cartilage during endochondral bone formation associated with increased osteoclastic activities. We tested the hypothesis that FOXO1 plays a key role in diabetes-impaired angiogenesis and chondrocyte apoptosis. Methods Closed fractures of the femur were induced in mice with lineage-specific FOXO1 deletion in chondrocytes. The control group consisted of mice with the FOXO1 gene present. Mice in the diabetic group were rendered diabetic by multiple streptozotocin injections, while mice in the normoglycemic group received vehicle. Specimens were collected 16 days post fracture. The samples were fixed, decalcified, and embedded in paraffin blocks for immunostaining utilizing anti cleaved caspase-3 or CD31 specific antibodies compared with matched control IgG antibody, and apoptosis by the TUNEL assay. Additionally, ATDC5 chondrocytes were examined in vitro by RT-PCR, luciferase reporter and chromatin immunoprecipitation assays. Results Diabetic mice had 50% fewer blood vessels compared to normoglycemic mice FOXO1 deletion in diabetic mice partially rescued the low number of blood vessels (p < 0.05). Additionally, diabetes increased caspase-3 positive and apoptotic chondrocytes by 50%. FOXO1 deletion in diabetic animals blocked the increase in both to levels comparable to normoglycemic animals (p < 0.05). High glucose (HG) and high advanced glycation end products (AGE) levels stimulated FOXO1 association with the caspase-3 promoter in vitro, and overexpression of FOXO1 increased caspase-3 promoter activity in luciferase reporter assays. Furthermore, we review previous mechanistic studies demonstrating that tumor necrosis factor (TNF) inhibition reverses impaired angiogenesis and reverses high levels of chondrocyte apoptosis that occur in fracture healing. Discussion New results presented here, in combination with recent studies, provide a comprehensive overview of how diabetes, through high glucose levels, AGEs, and increased inflammation, impair the healing process by interfering with angiogenesis and stimulating chondrocyte apoptosis. FOXO1 in diabetic fractures plays a negative role by reducing new blood vessel formation and increasing chondrocyte cell death which is distinct from its role in normal fracture healing.